Personal analytics and privacy : an individual and collective perspective : first international workshop, PAP 2017, Held in Conjunction with ECML PKDD 2017, Skopje, Macedonia, September 18, 2017, revised selected papers /: an individual and collective perspective : first international workshop, PAP 2017, Held in Conjunction with ECML PKDD 2017, Skopje, Macedonia, September 18, 2017, revised selected papers. (2017) - Unknown
No abstract available